A roadmap to the enzymes from spider venom: biochemical ecology, molecular diversity, and value for the bioeconomy - Dresler, Josephine; Avella, Ignazio; Damm, Maik; Dersch, Ludwig; Krämer, Jonas; Vilcinskas, Andreas; Lüddecke, Tim (Frontiers in Arachnid Science, 2024)
Spiders are ancient and highly successful predators, which use venom for both predation and defense. Their venoms are complex mixtures of potent biological molecules, emerging as a prolific source of biomolecular innovation in agriculture, biomedicine, and bioeconomy. While small cysteine-rich neurotoxins are typically considered the main components of spider venoms, recent research has shown that spider venoms also contain many high-molecular-weight proteins, especially enzymes. To date, very little is known about the diversity, biochemistry and ecology of these components. Here, we provide the first systematic overview of spider venom enzymes, describing all known examples in terms of their properties and functions in the spider venom system. We argue that the sheer diversity of these neglected spider venom compounds offers significant translational potential and holds great potential for the bioeconomy, reflecting a wide range of technical applications such as industrial production, food processing, and waste management.